2023
DOI: 10.1002/pssr.202300184
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Investigation of NO Molecule Adsorption on As6/Sb6 and Sb6/Bi6 Lateral Heterostructures

Abstract: Predicting and designing highly gas‐sensitive semiconductors is crucial for solving growing environmental problems. Herein, four lateral heterostructures (LHSs), As6/Sb6 AC‐/ZZ‐LHSs and Sb6/Bi6 AC‐/ZZ‐LHSs, are constructed. The adsorption of NO molecule on these LHSs is investigated using first‐principle calculations. The results indicate that the adsorption of NO molecule on As6/Sb6 LHS with armchair (AC) interface is physisorption, whereas NO molecule is chemically adsorbed on As6/Sb6 LHS with zigzag (ZZ) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The calculated lattice constants for the monolayers As, Sb, and Bi are 3.81 Å, 4.38 Å, and 4.58 Å, respectively. In our previous research within the research group, we evaluated the stability of all structures involved from the perspective of formation energy, demonstrating that the structures can exist spontaneously in a stable manner [ 44 , 45 , 46 ]. After optimization calculation, we found that the most stable adsorption sites of NO and NO 2 molecules on these three materials were located above the interface.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated lattice constants for the monolayers As, Sb, and Bi are 3.81 Å, 4.38 Å, and 4.58 Å, respectively. In our previous research within the research group, we evaluated the stability of all structures involved from the perspective of formation energy, demonstrating that the structures can exist spontaneously in a stable manner [ 44 , 45 , 46 ]. After optimization calculation, we found that the most stable adsorption sites of NO and NO 2 molecules on these three materials were located above the interface.…”
Section: Resultsmentioning
confidence: 99%
“…Chaurasiya et al effectively improved the adsorption strength of NO 2 and NO on MoSSe by introducing defects [18]. When a single homogenous material does not perform well in a device, it's a smart idea to introduce a heterojunction instead [19][20][21][22]. At present, the research on heterojunctions formed by MoSSe and other materials as gas sensing materials has not been carried out.…”
Section: Introductionmentioning
confidence: 99%